CUSTOMER RELATIONSHIP MANAGEMENT INDUSTRI MOBIL INDONESIA - WIBISONO SOEDIONO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
Implementation of Customer Relationship Management (CRM) strategy in the automobile industry by analyzing one of the dealers has gone well and has a considerable influence on the continuity of the company and also in maintaining its position as a market leader. The use of CRM in the company is important, although there are issues primarily from the substantial investment in the CRM application. It is important for companies to be able to build and get closer to the customer.